Use of Telemedicine to Improve Neonatal Resuscitation - Lee T. Donohue; Kristin R. Hoffman; James P. Marcin (MDPI AG, 2019)
Most newborn infants do well at birth; however, some require immediate attention by a team with advanced resuscitation skills. Providers at rural or community hospitals do not have as much opportunity for practice of their resuscitation skills as providers at larger centers and are, therefore, often unable to provide the high level of care needed in an emergency. Education through telemedicine can bring additional training opportunities to these rural sites in a low-resource model in order to better prepare them for advanced neonatal resuscitation. Telemedicine also offers the opportunity to immediately bring a more experienced team to newborns to provide support or even lead the resuscitation. Telemedicine can also be used to train and assist in the performance of emergent procedures occasionally required during a neonatal resuscitation including airway management, needle thoracentesis, and umbilical line placement. Telemedicine can provide unique opportunities to significantly increase the quality of neonatal resuscitation and stabilization in rural or community hospitals.